Taking the Heat : Women Chefs and Gender Inequality in the Professional Kitchen - Harris, Deborah Ann; Giuffre, Patti, 1966- (Book collections on Project MUSE., 2015)
A number of recent books, magazines, and television programs have emerged that promise to take viewers inside the exciting world of professional chefs. While media suggest that the occupation is undergoing a transformation, one thing remains clear: being a chef is a decidedly male-dominated job. Taking the Heat examines how the world of professional chefs is gendered, what conditions have led to this gender segregation, and how women chefs feel about their work in relation to men.